2013
DOI: 10.1111/vop.12047
|View full text |Cite
|
Sign up to set email alerts
|

Use of bovine pericardium (Tutopatch®) graft for surgical repair of deep melting corneal ulcers in dogs and corneal sequestra in cats

Abstract: Bovine pericardium graft offers a promising option for surgical reconstruction of the cornea following keratectomy for the management of corneal ulcers and sequestra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 54 publications
5
65
2
2
Order By: Relevance
“…Apart from recurrence and rejection, other reported FCS‐postoperative complications include residual pigment in CCT (1/17;6%) and in SIS grafts (3/5;60%), bacterial overgrowth in an AM graft (1/7;14%), and corneal ectasia in bovine pericardium grafting (1/3;33%) . In the present study, two eyes (11%) showed mild diffuse corneal pigment that resolved spontaneously, and one eye (5%) presented with graft malacia, which required a second keratoplasty, achieving good tectonic outcome and mild to moderate opacification.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Apart from recurrence and rejection, other reported FCS‐postoperative complications include residual pigment in CCT (1/17;6%) and in SIS grafts (3/5;60%), bacterial overgrowth in an AM graft (1/7;14%), and corneal ectasia in bovine pericardium grafting (1/3;33%) . In the present study, two eyes (11%) showed mild diffuse corneal pigment that resolved spontaneously, and one eye (5%) presented with graft malacia, which required a second keratoplasty, achieving good tectonic outcome and mild to moderate opacification.…”
Section: Discussionmentioning
confidence: 46%
“…Superficial keratectomy, although discouraged by some authors as a single procedure, can be performed when lesions affect less than 50% of the stromal depth . When the lesions are deeper (50–70% stromal depth), a grafting technique is required to strengthen the corneal structure, such as conjunctival grafting, corneoconjunctival transposition (CCT), biomaterial grafting [amniotic membrane (AM), bovine pericardium, porcine small intestinal submucosa (SIS)], or keratoplasty . Very deep (>70% stromal depth) and full‐thickness FCS have been previously treated with AM grafting, SIS, and keratoplasty, with variable outcomes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously reported treatments for feline corneal sequestrum include lamellar keratectomy alone or in conjunction with conjunctival autografts, corneoconjunctival transposition, or grafts of porcine small intestinal submucosa or urinary bladder acellular matrix, bovine pericardium, equine amniotic membrane, or fresh or frozen homologous or heterologous corneal tissue . Success rates for previously reported techniques are generally good but recurrences are seen with all techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions evaluated in the literature for feline corneal sequestrum include lamellar or full‐thickness keratectomy with or without a grafting procedure . Surgical time, procedure cost, duration of postoperative treatment, and final corneal clarity can vary significantly depending on the procedure performed.…”
Section: Introductionmentioning
confidence: 99%